Strength of reduced size mortarless interlocking Putra load bearing hollow block system - Mohd Ramly, Munirah (2015)
Industrialized building systems (IBS) was first introduced in Malaysia in the early 60’s as a prefabricated building systems. One of the five categories of IBS is the block wall building system. A mortarless interlocking hollow block (MIHB) wall system was developed in Malaysia by the Housing Research Centre of Universiti Putra Malaysia in 2001. The block system was named as Putra Block and it consists of three different units of block known as stretcher, corner and half block. Weight and strength of MIHB units are the most important properties that contribute to the strength of the block system. For Putra Block units, the average weight and strength of each block unit are 12 kg, 14 kg and 8 kg, and 17.2 N/mm2, 19.2 N/mm2, 17.0 N/mm2 respectively for stretcher, corner and half blocks. Based on these properties, the blocks have been considered as heavy; thus it leads to a higher strength capacity than the minimum requirement of load bearing walls for low rise housing. Subsequently, it leads to a higher overall construction cost for a building. There were number of previous researches that have been carried out in order to produce lighter blocks. However, it was found that none of the previous relevant research has been conducted on MIHB. In this study, the aim was to develop a lighter and more suitable MIHB for applications of load bearing walls in low rise housing while conforming to minimum strength requirement according to BS 5628. Therefore, one of the objectives is to optimize the materials content of MIHB concrete and to reduce the bearing area of MIHB in order to achieve the aim of this research. The concrete materials content to be optimized were the ungraded quarry dust content and cement content. The number of joints in the masonry wall was maintained during the reduction of bearing area size due to the fact that the joints are the weakest part in a masonry wall. The important parameters have been considered were the minimum width of block shell and slenderness of a typical concrete wall. The theoretical and experimental work have covered the design of masonry block, selection of optimum concrete mix for new size block, testing of individual block subjected to compressive load and testing of MIHB wall panel under vertical compressive load. The reduced size MIHB with optimum concrete mix design has been found to perform sufficient required strength for load bearing walls of low rise housing. As a result, material contents optimization has contributed to a reduction of 4% in weight with 27% reduction in strength of MIHB. Furthermore, a significant weight reduction has been attained by bearing size reduction which is 20% in weight with smaller losses of 5% in block strength. In summary, the combination of material contents optimization and bearing size reduction has significantly reduced the block weight meanwhile maintaining a sufficient strength capacity as load bearing blocks.